Memory extinction and spontaneous recovery shaping parasitoid foraging behavior. (30th June 2021) - de Bruijn, Jessica A C; Vet, Louise E M; Smid, Hans M; de Boer, Jetske G
Abstract: Animals can alter their foraging behavior through associative learning, where an encounter with an essential resource (e.g., food or a reproductive opportunity) is associated with nearby environmental cues (e.g., volatiles). This can subsequently improve the animal's foraging efficiency. However, when these associated cues are encountered again, the anticipated resource is not always present. Such an unrewarding experience, also called a memory-extinction experience, can change an animal's response to the associated cues. Although some studies are available on the mechanisms of this process, they rarely focus on cues and rewards that are relevant in an animal's natural habitat. In this study, we tested the effect of different types of ecologically relevant memory-extinction experiences on the conditioned plant volatile preferences of the parasitic wasp Cotesia glomerata that uses these cues to locate its caterpillar hosts. These extinction experiences consisted of contact with only host traces (frass and silk), contact with nonhost traces, or oviposition in a nonhost near host traces, on the conditioned plant species. Our results show that the lack of oviposition, after contacting host traces, led to the temporary alteration of the conditioned plant volatile preference in C. glomerata, but this effect was plant species-specific. These results provide novel insights into how ecologically relevant memory-extinction experiences can fine-tune an animal's foraging behavior. This fine-tuning of learned behavior can be beneficial when the lack of finding a resource accurately predicts current, but not future foraging opportunities. Such continuous reevaluation of obtained information helps animals to prevent maladaptive foraging behavior. Abstract : The parasitic wasp Cotesia glomerata temporarily ceases to respond to learned plant volatiles when the expected host caterpillar is not found, but only its traces, such as frass and silk. Such fine-tuning of learned behavior can be beneficial when the lack of host finding accurately predicts current, but not future opportunities. In this way, animals continuously re-evaluate available information to prevent maladaptive foraging behavior.